Immunochemotherapy of Cancer with Chlorambucil-carrying Antibody. Issue 5825 (26th August 1972) - Ghose, T.; Norvell, S. T.; Guclu, A.; Cameron, D.; Bodurtha, A.; MacDonald, A. S.
Abstract : Cell-surface localizing heterologous antibodies against the mouse EL4 lymphoma and a human malignant melanoma could be bound to chlorambucil without causing the loss of the alkylating activity of chlorambucil or interfering with the reactivity of the antibodies with their respective tumour cells. When given to mice preinoculated with tumour cells 2, 24, 72, and 120 hours before the beginning of treatment the chlorambucil-bound antibody was a much more effective tumour inhibitor than chlorambucil or the antibody alone. In a patient with disseminated malignant melanoma injection of the chlorambucil-bound anti-melanoma antibody first locally into a few metastatic nodules and then by the intravenous route was followed by the regression of all the metastatic nodules.